A robotic system for telementoring and training in laparoscopic surgery - Prince, Stephen W.; Kang, Christopher; Simonelli, James; Lee, Yu‐Hsiu; Gerber, Matthew J.; Lim, Christopher; Chu, Kevin; Dutson, Erik P.; Tsao, Tsu‐Chin (The international journal of medical robotics + computer assisted surgery, 2020)
A laparoscopic surgical training system, the LapaRobot, is introduced. The system is composed of an expert station and a trainee station connected through the Internet. Embedded actuators allow the trainee station to be driven by an expert surgeon so that a trainee learns proper technique through physical feedback. The surgical‐tool trajectory and video feed can be recorded and later “played back” to a trainee to hone operative skills through guided repetition without the need for expert supervision. The system is designed to create a high‐fidelity approximation of the intracorporeal workspace, incorporate commercially available surgical instruments, and provide a wealth of high‐resolution data for quantitative analysis and feedback. Experimental evaluation demonstrated a 55% improvement in surgical performance with use of our system. In this paper, we introduce the details of the design and fabrication of the LapaRobot, illustrate the mechatronics and software‐control schemes, and evaluate the system in a study.